Analisis Peluang Usaha UMKM Makanan Tradisional di Desa Pallangga Kecamatan Pallangga Gowa - Imaduddin Imaduddin; Amirullah, Amirullah (STIPAS Tahasak Danum Pambelum Keuskupan Palangkaraya, 2023)
The aim of this service is to provide guidance to the community in Pallangga Village, Pallangga District, to increase their understanding of the economic value of Micro, Small and Medium Enterprises (MSMEs), especially in the context of the traditional food